Modeling the Relationship Between Concerns and Environmental Attitudes Among Students, University of Agricultural Sciences and Natural Resources Khuzestan, Iran - Abolmohammad Bondori; Masoumeh Forozani; Fatemeh Ghasemzadeh (محیط زیست و مهندسی آب)
One of the desirable solutions to overcome environmental challenges is the education and training of academic-educated human resources holding an environmental perspective. Therefore, the aim of the present research was to model the relationship between concerns and environmental attitudes of students at the Agricultural Sciences and Natural Resources University of Khuzestan. The statistical population of this study included students enrolled and actively studying at this university during 2022-2023. The sample size of 161 was determined using the Cochran formula, and sampling was done using the proportional stratified-random manner. Findings indicated that 72% of the variance in students' environmental attitudes was predicted by environmental concerns. Moreover, environmental concern variables significantly modeled students' attitudes toward the environment. Therefore, to improve agricultural students’ attitude, influential figures such as pro-environmental academic members and other well-known individuals could hold seminars at universities discussing the importance of environmental conservation. and by delivering speeches at university seminars on promoting respect and environmental conservation. This could potentially shift students' perspectives on the environment, leading to an increased positive attitude towards environmental protection.